The Evaluation Of Drug Storage at The Pharmacy Warehouse Gamping 1 Health Center, Sleman Regency - Syahyeri, Afrizal (Journal of health research and technology, 2025)
Introduction: Pharmaceutical services at community health center include 2 (two) activities include the management of pharmaceutical preparations and consumable medical materials and clinical pharmacy service activities. One of the pharmaceutical preparation management activities is drug storage. Drug storage is one way to guarantee the quality of drugs so that they are safe. Objective: To evaluate the drug storage at the Gamping 1 Health Center, Sleman Regency. Methods: This research design is a descriptive non-experimental study using a cross sectional approach. Using a checklist sheet guided by the Regulation of the Indonesian Minister of Health Regulation of the Minister of Health of the Republic of Indonesia No. 74 of 2016 and the Technical Guidelines for Pharmaceutical Service Standards in 2019 to evaluate the drug storage and Satibi (2014) to compare the efficiency of drug storage. Results: Percentage of the suitability of drug storage was 85.71% and the suitability of the drug storage process was 88.88%. The results of storage efficiency obtained standard results indicators, namely the Turn Over Ratio (TOR) value of 4.10 times/year, the percentage of expired drugs was 5.88% with total loss is IDR 1,734,546.50, the percentage of damaged drugs was 0%, the percentage of drug dead stocks are 13.07%, the drug suitability with stock cards amount 78.95%, the percentage of final stock of drugs was 24.39%. Conclusions: The suitability of drug storage space and drug storage process in the pharmaceutical warehouse of Puskesmas Gamping 1 Sleman Regency is quite good but has not met the 100% standard. The efficiency of drug storage have not met the standards.